RESEARCH THE PROJECTS CHARACTERISTICS IN THE SPHERE OF UNIVERSITIES’ PHYSICAL EDUCATION AND SPORTS ACTIVITIES - Plakhin , Andrey; Kocherian, Maksim; Volovik, Tatiana (Revista Inclusiones, 2020)
The purpose of the study is to develop methodological tools for assessing the projects effectiveness in terms of network interaction strategies of universities. The authors, sequentially summarizing the value, process and resource approaches to the formation of a methodology for assessing projects of sports and athletic activities of a university offer a comprehensive methodology. The results of the study show that the universities of the Sverdlovsk region (Russian Federation) are characterized by network interaction projects related to regional events, while there is no network interaction in the field of training students and the formation of common competencies in the field of physical culture and sports.